2019
DOI: 10.37469/0507-3758-2019-65-6-904-919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the Tumor-Initiating Stem Cells Eradication Strategy on the Example of Human Glioblastoma Cell Line U87

Abstract: The effectiveness of the new therapeutic approach aimed at the destruction of the cancer cell community was evaluated on the immortalized human glioblastoma cell line U87. Initially, the reference elements of a new strategy for eradication of tumor-initiating stem cells were characterized. The main points of the strategy were as follows. 1) Evaluation of the TAMRA+ (tumor-initiating stem cells) presence in the population of U87 culture cells. 2) Determination of the reference time points of the DNA interstrand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…In parallel, addition of the DNAmix leads to a massive lysis of committed cancer cells. This technology has been successfully tested on several experimental mouse and human cancers and in 3 pilot clinical cases (6,8,(76)(77)(78)(79).…”
Section: Cmld Cp-based Chemotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…In parallel, addition of the DNAmix leads to a massive lysis of committed cancer cells. This technology has been successfully tested on several experimental mouse and human cancers and in 3 pilot clinical cases (6,8,(76)(77)(78)(79).…”
Section: Cmld Cp-based Chemotherapymentioning
confidence: 99%
“…At the core of Karanahan technology and CMLD CP-based chemotherapy is the use of DNAmix and CP. Their combination is rationally motivated and has been shown to be effective in “incurable” cancers, such as Krebs-2, U-87 xenografts, and B cell lymphomas in mice ( 6 , 8 , 78 , 80 , 81 ).…”
Section: Dnamix and Cp Treatments Are Core Elements Of The Karanahan Technology And Cmld Cp-based Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, it can be concluded that low/medium-dose intermittent metronomic CP chemotherapy, which relies on both the timing of repairing CP-induced DNA ICLs and that of TISCs synchronization (a variant of Karanahan , but without the use of DNA-mix), has 3 special features to mention. Triple consecutive exposures to CP results in (1) large-scale apoptosis of the bulk of tumor cells independently on tumor type and origin 55 , 56 ; (2) synchronization of tumor cells (including TISCs) and their accumulation in G2/М with following transition into G1, which is observed as shifts in cell cycle peaks 57 (on the day when TISCs synchronously exit the cell cycle arrest, the terminal exposure to CP, leading to either complete or significant eradication of TISCs, 58 , 59 is administered); and (3) depletion of immunosuppressive regulatory T cells, repolarization of myeloid-derived suppressor cells to tumor reactive one and consequent activation of effector lymphocytes. 53 , 54 …”
Section: Introductionmentioning
confidence: 99%